Exactly Median-Unbiased Estimation of First Order Autoregressive/Unit Root Models - Andrews, Donald W. K. (Econometrica, 1993)
First-order autoregressive/unit root models with independent identically distributed normal errors are considered, including those without an intercept, those with an intercept, and those with an intercept and time trend. The autoregressive parameter is allowed to lie in the interval (-1, 1], which includes the unit root case. Exactly median-unbiased estimators and exact confidence intervals of the autoregressive parameter are introduced. Corresponding exactly median-unbiased estimators and exact confidence intervals are also provided for the impulse response function, the cumulative impulse response, and the half life of a unit shock. An unbiased model selection procedure is discussed. The introduced procedures are applied to several data series. Copyright 1993 by The Econometric Society.